Maldives : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Maldives. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that the main challenge for Maldives is to contain fiscal expenditures that have increased sharply following the tsunami. Expenditure has reached extraordinarily high levels by international and historical standards, with the majority of the increase in domestically financed expenditure unrelated to the tsunami. Executive Directors were encouraged that Maldives' economy has rebounded strongly from the December 2004 tsunami. Directors have commended the authorities for implementing the Maldives Monetary Authority Act by appointing an independent governor.